An Efficient Hybrid Approach in Solving the Multiple Postman Problem - Shakir Hameed, Asaad; Mohd Aboobaider, Burhanuddin; Hea Choon, Ngo; Habib Bilal, Wassim; Lafta Mutar, Modhi (International Journal of Engineering and Technology, 2018)
In this study, the proposed algorithm contributed to the enhancing of solutions of the Multiple Postman Problem m-PP, which is one of the optimization problems that, has attracted a lot of attention at the present time. It is a problem of the NP-hard type. However, because of the complication of polynomial time, there is still no algorithm providing us with the optimal solution of this problem. All the used algorithms give solutions that are close to the optimal one. In this research, we will present the Hybrid Algorithm HA in two phases. In the first phase the Sweep Algorithm SW is applied, and in the second one, the Ant Colony Algorithm and the local search 3-opt are applied. we will then compare the quality of the solution resulted from this hybrid approach with the results of well-known standard tests to determine the effectiveness of the presented approach.Â Â